Oltre il sistema di accoglienza. La transizione abitativa dei rifugiati nella città di Milano - Giuseppe Gambazza; Flavio Lucchesi; Maria Paradiso (Bollettino della Società Geografica Italiana)
This study is anchored on the perspective of local turn in migrant integration, which requires cities to play an increasingly important role in defining public policies. Consequently, the research focuses on the explorative case of the city of Milan, aiming to demonstrate whether its local system provides a toolbox for refugees to promote their integration in the host/majority milieus. Through a qualitative method, based on semi-structured interviews with politicians, local officers, NGO activists, volunteers, and refugees, we will try to understand élite and non-élite perspective about how and where the refugees of the reception system of Milan can find an accommodation, at the end of the institutional process. In this way, it will also be possible to understand how the municipality is facing the restrictions to the Italian asylum system, the crisis of the welfare, the market-dominated systems of housing provision and the suspiciousness or racism towards immigrants, considered as a burden or a threat for the society.